The Role of the Language Environment in Improving Arabic Learning Abilities - Faizal Pikri (International Journal of Science and Society, 2022)
One factor that influences and determines the success of the learning process is the environment, and the language environment is no exception. A quality language environment is significant for the success of someone learning a second language, in this case, Arabic. In this paper, the author wants to discuss the role of the language environment in improving Arabic learning skills. This research uses qualitative research. The qualitative research approach is a research and understanding process based on a methodology that investigates a social phenomenon and human problem. The results of the study show that the language environment plays an essential role in improving Arabic language skills because the language environment is designed in such a way that it is similar to the original environment so that there is an appreciation and supportive attitude towards learning Arabic from related parties so that it creates student motivation in learning Arabic. There are ten strategies to develop an Arabic learning environment, namely the formulation of a mission, strong commitment, reviewing the Arabic curriculum, determining Arabic language compulsory days, Arabic seminars, nuanced Arabic competitions, providing adequate Arabic language media, dormitory concepts with Arabic nuances, cooperation between institutions and the provision of rewards for achievers.